Corpus-based study of lexical bundles in academic lectures across three disciplinary divisions - Kashiha, Hadi (2015)
Simply defined as extended collocations, lexical bundles are combination of more than two words which co-occur frequently in a given register (Biber et al., 1999). They lead to coherence in text or speech and play a key role in fluent linguistic production. Recent decades have witnessed an increasing body of research on lexical bundles; however, there is still a question of whether these expressions are used differently in academic speech of different disciplinary divisions. To this aim, this study investigates and compares the frequency, structure and discourse function of the most frequently occurring four-word lexical bundles in academic lectures across three broad disciplinary groupings, namely social sciences, physical sciences and life and medical sciences. This comparative study was run on the nearly one million word corpus of 120 academic lectures (40 from each science). The lectures were transactional in nature and sourced from British Academic Spoken English (BASE) corpus. The most frequent four-word bundles were identified in each corpus using the computer program WordSmith Tools 5 (Scott, 2008). Then, the structural and functional taxonomies proposed by Biber et al. (2004) were used as analytical frameworks to group lexical bundles in terms of their grammatical types and the discourse functions they serve. Primary findings revealed some variations between the three sciences in relation to the distributional patterns of the target bundles. In addition, the three groups of lecturers also showed different tendencies towards the selection of grammatical types to form lexical bundles and the functions that the bundles carried out in academic lectures. The results suggest that the selection of bundle types and the way they are used to fulfill disciplinary functions in the academic lectures are to a large extent disciplinary-bounded. Some bundles were also found to be specific to each corpus. Disciplinary lecturers appeared to have their own specific ways of selecting lexical bundles to convey disciplinary materials in a way to be as comprehensible as possible for the audiences. Based on the obtained results, it can be suggested that lexical bundles are considered as a pivotal means in distinguishing the academic speech of different fields of studies. The implication of this study direct itself to the novice (especially those working in ESL/EFL settings) academic lecturers belonging to sciences under investigation. Findings of this study open more windows to how lexical bundles and their communicative functions are employed in academic disciplinary lectures. Students who study in these sciences could also benefit from findings of this research by being familiarized with the structural and functional characteristics of lexical bundles.